2020
DOI: 10.13106/jafeb.2020.vol7.no7.369
|View full text |Cite
|
Sign up to set email alerts
|

Determinants Influencing Entrepreneurial Intention among Undergraduates in Universities of Vietnam

Abstract: The paper aims to identify the determinants that influence entrepreneurial intention among National Economics University graduates. For the sample size, we conducted a questionnaire survey of 250 full-time third-year undergraduates at the National Economics University, with convenience sampling technique. Of those 250 undergraduates, 150 were Business Administration students and 100 Economy Management students. After eliminating invalid responses due to lack of information or low quality information, 215 respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 30 publications
9
55
0
5
Order By: Relevance
“…The result of this study which reveals a positive and significant relationship between the attitude, perceived behavioural control and entrepreneurship education towards entrepreneurial intention is consistent with the previous findings by Rudhumbu et al (2016), Alexander & Honig (2016), Mahmood, Al Mamun, Ahmad, & Ibrahim (2019) and Bui et al (2020). However, an insignificant relationship of self-efficacy towards entrepreneurial intention was found in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The result of this study which reveals a positive and significant relationship between the attitude, perceived behavioural control and entrepreneurship education towards entrepreneurial intention is consistent with the previous findings by Rudhumbu et al (2016), Alexander & Honig (2016), Mahmood, Al Mamun, Ahmad, & Ibrahim (2019) and Bui et al (2020). However, an insignificant relationship of self-efficacy towards entrepreneurial intention was found in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Entrepreneurial skills, for instance, the abilities of the entrepreneur to develop plans and anticipate obstacles, take proactive actions to reap opportunities or preventing a failure, and work efficiently, would foster individuals to feel competent and venture into entrepreneurship (Scherer et al, 1991). A study by Bui et al (2020) also shows that among graduates in Vietnam universities who had taken an entrepreneurship course, had shown a greater tendency to become entrepreneurs. Another study by Mahmood, Zahari, Ibrahim, Nik Jaafar and Yaacob (2020) found that entrepreneurship curriculum at the university has facilitated the students in doing their business effectively due to the knowledge and skills learned.…”
Section: Entrepreneurship Education (Ee)mentioning
confidence: 99%
“…Factors that mediate entrepreneurial learning to entrepreneurial intention is the theory of planned behavior (Ajzen, 1991;Zhang et al, 2019;Bui et al, 2020), the theory consists of attitude toward behavior, subjective norm, and perceived behavioral control. These factors will influence the entrepreneurial intention of individuals.…”
Section: Literature Review and Hypohtesismentioning
confidence: 99%
“…Entrepreneurship for the younger generation can be grown through entrepreneurship education that fosters entrepreneurial intentions. Perceived desirability is the most influential factor in fostering entrepreneurial intentions by starting a business (Bui et al, 2020) Skills in entrepreneurship demonstrate an ability to create something new and different. Innovation and creativity as capital in cooperation and competition.…”
Section: Entrepreneurial Skillsmentioning
confidence: 99%